The complete mitogenome of the Australian crayfish Geocharax gracilis Clark 1936 (Crustacea: Decapoda: Parastacidae). (3rd March 2016) - Gan, Han Ming; Tan, Mun Hua; Gan, Huan You; Lee, Yin Peng; Schultz, Mark B.; Austin, Christopher M.
Abstract: The mitogenome of the black yabby, Geocharax gracilis, was sequenced using the MiSeq Personal Sequencer. It has 15, 924 base pairs consisting of 13 protein-coding genes, 2 ribosomal subunit genes, 23 transfer RNAs, and a non-coding AT-rich region. The base composition of G. gracilis mitogenome is 32.18% for T, 22.32% for C, 34.83% for A, and 10.68% for G, with an AT bias of 67.01%. The mitogenome gene order is typical for that of parastacid crayfish with the exception of some minor rearrangements involving tRNA genes.